Frictional characteristics of the newer orthodontic elastomeric ligatures - A V Arun; Anna Cecilia Vaz (Wolters Kluwer Medknow Publications, 2011)
Introduction: Elastomeric ligatures reduce chairside time but increase friction. Polymeric coatings and 45° angulations have been introduced to the ligature modules to combat its disadvantages and reduce friction. This in vitro study compared the frictional characteristics of six different types of the most commonly used elastomeric modules. Materials and Methods: Thecoefficient of friction for six ligation methods: the non-coated Mini Stix† and coated Super Slick Mini Stix™ (TP Orthodontics), 45° angulated but non-coated Alastik Easy-To-Tie™ (3M Unitek) elastomerics and non-angulated non-coated Alastik QuiK-StiK FNx01 , 0.110'- and 0.120'-diameter elastomerics™ (Reliance Orthodontics) were measured in dry conditions utilizing a jig according to the protocol of Tidy. Results: A significant difference was observed between the various types of elastomeric ligatures (P<.01). Among the six types of elastomeric ligatures, the 45° angulated elastomeric ligatures produced the least friction, followed by the coated Super Slick† elastomers. No difference in the friction was noted when the diameter of the elastomeric ligatures was varied. Conclusions: Polymeric surface coatings and introduction of angulations into elastomeric ligatures reduce the friction during sliding; however, the diameter of the ligature made no difference to sliding friction.